2009
DOI: 10.1016/j.jconrel.2008.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Polymersome delivery of siRNA and antisense oligonucleotides

Abstract: siRNA and antisense oligonucleotides, AON, have similar size and negative charge and are often packaged for in vitro delivery with cationic lipids or polymers–but exposed positive charge is problematic in vivo. Here we demonstrate loading and functional delivery of RNAi and AON with non-ionic, nano-transforming polymersomes. These degradable carriers are taken up passively by cultured cells after which the vesicles transform into micelles that allow endolysosomal escape and delivery of either siRNA into cytoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(104 citation statements)
references
References 57 publications
(95 reference statements)
2
99
0
3
Order By: Relevance
“…Cerritelli et al (2007) have shown that using a protease-sensitive sulfur bridge polymersome, cytosolic delivery can be achieved. Similarly Ahmed and coworkers have shown that the endocytic degradative environment can favor cytosolic delivery using hydrolyzable polymersomes (Ahmed et al 2006;Kim et al 2009). pH-sensitive polymersomes have also been proposed by the Battaglia group using poly(2-[diisopropylamino] ethyl methacrylate) (PDPA) (Lomas et al 2007(Lomas et al , 2008Massignani et al 2010).…”
Section: Endosome Escape Strategiesmentioning
confidence: 93%
“…Cerritelli et al (2007) have shown that using a protease-sensitive sulfur bridge polymersome, cytosolic delivery can be achieved. Similarly Ahmed and coworkers have shown that the endocytic degradative environment can favor cytosolic delivery using hydrolyzable polymersomes (Ahmed et al 2006;Kim et al 2009). pH-sensitive polymersomes have also been proposed by the Battaglia group using poly(2-[diisopropylamino] ethyl methacrylate) (PDPA) (Lomas et al 2007(Lomas et al , 2008Massignani et al 2010).…”
Section: Endosome Escape Strategiesmentioning
confidence: 93%
“…A similar approach to protect and deliver bioactive molecules is their incorporation within polymersomes. [126][127][128] Polymersomes are bilayer membrane capsules formed through the self-assembly of ampiphilic block copolymers. 129 Biodegradable functionalized polymersomes exhibit potential for site-specific therapeutic delivery through incorporation into PEMs.…”
Section: Multifunctional Pems For Tissue Engineeringmentioning
confidence: 99%
“…29 Probability of the absence of a detectable level of output proteins from the NAND gate for different levels of both inputs nucleic acids and proteins, some of which have proven useful as bioreactors, drug delivery vehicles or as earlystage protocells (Noireaux and Libchaber 2004;Meng et al 2009;Roodbeen and van Hest 2009;van Dongen et al 2009). For instance, some of the amphiphiles employed for the encapsulation of DNA show interesting properties such as the ability to respond to an external stimuli, such as pH (Lomas et al 2007;Kim et al 2009). Among those, we have focussed attention on the PEG-PLA system developed by Discher et al (Kim et al 2009).…”
Section: Potential Routes To a Chemical Implementationmentioning
confidence: 99%
“…For instance, some of the amphiphiles employed for the encapsulation of DNA show interesting properties such as the ability to respond to an external stimuli, such as pH (Lomas et al 2007;Kim et al 2009). Among those, we have focussed attention on the PEG-PLA system developed by Discher et al (Kim et al 2009). for which, the vesicle cargo can be gradually released as a function of the pH, due to the formation of pores in the vesicle membrane, as a result of the hydrolysis of the polyester block (Ahmed and Discher 2004).…”
Section: Potential Routes To a Chemical Implementationmentioning
confidence: 99%